123k views
0 votes
What is the correct order of operations for simplifying the expression (x+3)^2-(x^2+9)/2x^2

2 Answers

4 votes

((x+3)^2-(x^2+9))/(2x^2)\\\\use\ (a+b)^2=a^2+2ab+b^2\\\\=(x^2+2\cdot x\cdot3+3^2-x^2-9)/(2x^2)=(x^2-x^2+6x+9-9)/(2x^2)\\\\=(6x)/(2x^2)=(3)/(x)
User Raga
by
5.4k points
3 votes

Answer with explanation:

The correct order of simplifying the expression is:

1. Opening the bracket Using Identity

2. Adding and Subtracting Like terms

The given expression is


=((x+3)^2-(x^2+9))/(2x^2)\\\\=(x^2+6 x+9-x^2-9)/(2x^2)\\\\=(6x)/(2x^2)\\\\=(3)/(x)\\\\ \text{Used the identity and law of indices}\\\\(a+b)^2=a^2+2 a b+b^2\\\\ (x^a)/(x^b)=x^(a-b)

User Gnaural
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.